Evaluation of cellular toxicity of three denture base acrylic resins. - M Ebrahimi Saravi; M Vojdani; F Bahrani (Tehran University of Medical Sciences, 2012)
This study aimed to evaluate the cellular toxicity of two newly-released acrylic resins (Futura Gen and GC Reline Hard) in comparison with the conventional heat-cure resin (Meliodent).Sample discs from each acrylic resin were placed in 24-well culture plates along with L929 mouse fibroblast cell line. A mixture of the RPMI 1640 medium, antibiotics and 10% FBS was added to the plates and the specimens were incubated in a CO(2) incubator. The amount of light absorption by each plate was determined after 1 hour, 24 hours and 1 week by the MTT assay and ELISA. The cytotoxic effect of the resins was compared among groups using the two-way ANOVA and further paired comparison was performed using the post-hoc Tukey's test.After 1 hour, Futura Gen displayed a significantly lower level of light absorption in comparison with Meliodent (P=0.03). After 24 hours, GC Reline Hard rendered a significantly lower level of light absorption compared to Meliodent (P=0.02). After one-week of incubation, the mean absorption rates for GC Reline Hard, Meliodent and Futura Gen were relatively similar (P>0.05). The lowest and highest level of cytotoxicity among all resins were observed after one week and 1 hour of immersion in water, respectively.All the tested resins induced some degree of cytotoxicity. Cytotoxicity of Futura Gen, GC Reline Hard and Meliodent resins failed to show any significant reduction from 24 hours to one week. Thus, it is recommended to immerse the dentures in water for 24 hours prior to delivery to the patient.